2018
DOI: 10.1155/2018/7028267
|View full text |Cite
|
Sign up to set email alerts
|

Selected Biomarkers Correlate with the Origin and Severity of Sepsis

Abstract: The microbial etiology and source of sepsis influence the inflammatory response. Therefore, the plasma levels of cytokines (IL-6, IL-8, and IL-10), chemokines (CCL2/MCP-1, MIP-1β), heparin-binding protein (HBP), soluble CD14 (sCD14), and cortisol were analyzed in blood from septic patients obtained during the first 96 hours of intensive care unit hospitalization. The etiology was established in 56 out of a total of 62 patients enrolled in the study. Plasma concentrations of MCP-1, sCD14, IL-6, and IL-10 were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 45 publications
0
20
0
1
Order By: Relevance
“…In another study, baseline cytokine concentrations were measured using Luminex TM analysis; the results showed that serum MCP-1 levels in healthy males and females were 62.8 and 55.4 pg/mL, respectively. In children with meningococcal sepsis, serum MCP-1 levels were positively correlated with SOFA scores (r = 0.68), and in adults who died of sepsis, serum MCP-1 levels were meaningfully higher than those in survivors [107,108].…”
Section: Biomarkers Of Sepsismentioning
confidence: 99%
“…In another study, baseline cytokine concentrations were measured using Luminex TM analysis; the results showed that serum MCP-1 levels in healthy males and females were 62.8 and 55.4 pg/mL, respectively. In children with meningococcal sepsis, serum MCP-1 levels were positively correlated with SOFA scores (r = 0.68), and in adults who died of sepsis, serum MCP-1 levels were meaningfully higher than those in survivors [107,108].…”
Section: Biomarkers Of Sepsismentioning
confidence: 99%
“…[7][8][9] Determining biomarkers for cytokine storms that meet the needs of early clinical diagnosis, risk stratification, therapeutic response monitoring, and prognosis evaluation has been a continuous goal of JOURNAL OF TRANSLATIONAL INTERNAL MEDICINE / APR-JUN 2020 / VOL 8 |ISSUE 2 researchers. [10][11][12][13] The time course of cytokine storms could, to a certain degree, be used to guide the clinical treatment. This study aimed to explore the characteristics of cytokine storm in patients with septic shock after abdominal surgery, examine its relationship with hemodynamics, and determine appropriate intervention timings for cytokine storms.…”
Section: Introductionmentioning
confidence: 99%
“…Biomarkers often represent only indicators of renal cell damage (Beker et al, 2018). In contrast, molecules involved in inducing the damaging insult are of much greater importance to be identified (Holub et al, 2018;Oberbauer, 2008). Inactivation and elimination of such toxic compounds originating mostly from endogenous production would be the highest priority.…”
Section: Introductionmentioning
confidence: 99%
“…Inactivation and elimination of such toxic compounds originating mostly from endogenous production would be the highest priority. Among those molecules inflicting damage at the renal microvascular structures and the proximal tubule are interleukins and proteases as well as neutrophil extracellular traps (NET) (Denning et al, 2019;Holub et al, 2018;Kumar et al, 2019). Many of them are secreted from effector cells and act as eliminators against the invading pathogens (Brinkmann et al, 2004).…”
Section: Introductionmentioning
confidence: 99%